The Jarimatika Method in Improving Multiplication Calculation Skills in Mathematics for Elementary School Students - LESTARI, LILIS; Ulya, Vita Fitriatul; Khumaimah, Rinatul (Universitas Islam Lamongan, 2024)
This research aims to explain the effectiveness of the jarimatika method in improving the multiplication skills of second-grade students in mathematics at SDI Al Hadad Kedungjambe Singgahan Tuban. This study is classified as qualitative research. Data collection techniques include observation, interviews, and documentation. The research results show that the jarimatika method can improve student learning outcomes in multiplication material. The application of the Jarimatika method in the second grade at SDI Al Hadad Kedungjambe Singgahan Tuban shows that implementing the Jarimatika method significantly improves various aspects of mathematics learning. There is an increase in student active participation from 45% to 85%, multiplication accuracy rising from 50% to 90%, calculation speed with the average time to complete multiplication problems reduced from 10 minutes to 5 minutes, and student confidence rising from 40% to 80%. Additionally, the number of students achieving the Minimum Competency Criteria (KKM) significantly increased after applying this method. Inhibiting factors include students being noisy, often chatting, and lacking understanding. Supporting factors include the ease and practicality of using the jarimatika method and the teacher’s ability to effectively manage and condition the class.